Correlation between Ascites and Total Lymphocyte Count with Occurrence of Hepatic Encephalopathy in Liver Cirrhosis Patients - Ratna Adelia Pravitasari (Fakultas Kedokteran Universitas Brawijaya, 2021)
Hepatic encephalopathy (HE) is brain dysfunction manifested as a broad spectrum of neuropsychiatric abnormalities caused by hepatic insufficiency or portosystemic shunting due to portal hypertension. Portal hypertension in liver cirrhosis also causes ascites, as the most common clinical manifestation. Further, immune dysfunction, one of which is decreased total lymphocyte count (TLC), happens at liver cirrhosis, which triggers the systemic inflammatory response. This systemic inflammatory response plays a role in HE. Objective of this study is to know the correlation between ascites and TLC with occurence of HE in liver cirrhosis patient. This study was conducted by retrospective cohort design in Saiful Anwar Hospital. Determination of sample amount at this study used total sampling method. Hepatic encephalopathy diagnosis was based on West Haven Criteria. Ascites was determined by physical examination and/or abdominal ultasonography. Total lymphocyte count data was taken from medical record, with complete blood count examination used XS-800i hematology analyzer machine. Data were analyzed using a logistic regression test, with p<0.05 was considered significant and Confidence Interval (CI) 95%. Seventy-eight liver cirrhosis patients were observed using a retrospective cohort method regarding the HE occurrence, and physical examination for ascites and laboratory examination were performed. The statistical analysis result of the correlation between ascites and HE is significant with an odds ratio of 5.108 and CI of 1.36-19.25. On the other hand, TLC has no significant correlation with the occurrence of HE. Based on this analysis result, it is concluded that ascites has a correlation with HE, but TLC does not.Â